Hubungan Berat Badan Lahir dengan Status Gizi Bayi 1-6 Bulan Berdasarkan Indeks Bb/U di Tpmb Evi Fitrianti Tahun 2025: Relationship Between Birth Weight and Nutritional Status of Infants Aged 1-6 Months Based on the Bb/U Index at Tpmb Evi Fitrianti in 2025 - Delsy Dianita; Mia Dwi Agustiani; Dian Monalisa Rusliani (Journal of Health, 2026)
Background: Infant malnutrition remains a global public health problem, with 12.3% of infants worldwide affected according to the 2024 Joint Malnutrition Estimates. Birth weight is an important determinant of infant nutritional status and growth, therefore, this study examines the relationship between birth weight and the nutritional status of infants aged 1-6 months based on the BW/A index at TPMB Evi Fitrianti in 2025. Methods: This quantitative cross-sectional observational analytic study involved 32 infants aged 1-6 months selected by total sampling, with data collected from questionnaries, infant weight measurements, and KIA books or medical records, and analyzed using univariate analysis and Fisher’s Exact Test. Results: The majority of 3-month-old respondents (25.0%) were female (68.8%), and were breastfed (78.1%). Most infants (90.6%) were born with normal birth weight (BW), while 9.4% were classified as low birth weight (LW). The nutritional status of infants was generally good (93.8%), although 6.3% were classified as malnourished. Fisher's exact test showed a significant relationship (p = 0.006 < 0.05) between BW and nutritional status. Low birth weight infants are at higher risk of malnutrition due to immature energy reserves and immune systems. Conclusion: There is a significant relationship between BW and nutritional status of infants aged 1-6 months, based on the BW/A index. Low birth weight infants are at higher risk of malnutrition. Early monitoring and intervention are needed to improve nutritional status, especially in low birth weight infants.